Ríos y embalses bajo el sol - Marcé Romero, Rafael (My University, 2015)
The importance of water resources stored in reservoirs on a global scale is not matched with a sound knowledge of the possible impacts of climate change on reservoir water quality. This is especially relevant in the Mediterranean regions, where most countries rely on reservoirs to fulfill their water supply needs, and virtually all climate models predict increasing water shortage in the next 20 years. In this talk I summarize recent findings that stress the profound differences between lakes and reservoirs concerning their responses to global changes. The main conclusion is that application of the lake tool kit to solve management problems in reservoirs may lead to the wrong decisions, and we challenge the general empirical formulations and models usually applied in lakes with patterns observed in Mediterranean reservoirs that seem to apply at global scales. To exemplify this, I use long term data collected during 45 years in Sau Reservoir, the location of the most influential studies by Dr. Joan Armengol, and an inspiration for a generation of reservoir limnologists.
Keywords: Embalses; Ecología; Ríos; Biogeoquímica; Limnología